Polymeric Approach to Adjuvant System in Antibody Production against Leishmaniasis Based on Hybridoma Technology - Yildiz, Asli Pinar Zorba; Koken, Gulnaz Yildirim; Abamor, Emrah Sefik; Bagirova, Melahat; Tosyali, Ozlem Ayse; Kocagoz, Tanil; Allahverdiyev, Adil (IRANIAN SCIENTIFIC SOCIETY MEDICAL ENTOMOLOGY, 2022)
Background: Leishmaniasis is a zoonotic disease, which is one of the serious public health problems in the world. Nowadays, antibody production using hybridoma technology may be a correct approach in terms of sensitivity in the diagnosis of diseases such as leishmaniasis. The aim of this study was investigation of the effectiveness of different adjuvants on polyclonal antibody production against L. tropica based on hybridoma technique.Methods: Accordingly, Freund's adjuvant (1956, M. tuberculosis), as a classic adjuvant in studies, was used comparatively with the non-toxic polymeric based Polyoxidonium adjuvant. All animal immunization procedures were conducted at Bezm-i Alem University Experimental Animal Research Center. The adjuvant response was tested both in the serum sample and in the antibodies produced by the hybridomas. The antibody titers were determined with ELISA.Results: Freund's and Polyoxidonium (PO) group blood titer's increased approximately 5.5 fold compared to control after the 6(th) and 8(th) immunization. Hybridomas produced from mice immunized with PO adjuvant induced only antigen-specific antibody response and did not develop an immune response against the adjuvant.Conclusion: Adjuvant selection is very important in terms of the specificity of antibody responses of cells produced in hybridoma technology. Therefore, PO is recommended as a new adjuvant system in this study.
Keywords: Leishmaniasis; Antibody; Hybridoma technology; Adjuvant; Vaccine; LINKED-IMMUNOSORBENT-ASSAY; DIRECT AGGLUTINATION-TEST; VISCERAL LEISHMANIASIS; MONOCLONAL-ANTIBODIES; DIAGNOSIS; POLYOXIDONIUM; PROMASTIGOTES; SERODIAGNOSIS; CULTIVATION; Parasitology